The moderating role of organizational size between the Malaysian cultural orientation, Islam Hadhari's principles and reward management practices: A study in Malaysian private organizations - Wan Mohd Noor, Wan Shakizah; Quaddus, Mohammed; Mohd Isa, Mohd Faizal; Daud, Zulkiflee (2012)
Many best practice models exist that describe successful approaches to reward management which influence by the cultural, legal, organizational and administrative challenges in Islamic world.Thus, the decision in setting and designing reward programs in raising productivity through human effort has always been controversial. Studies that were undertaken in numerous countries have shown varying degrees of success of such practices.Even though there is a substantial amount of foreign literature on this subject, there is a paucity of information concerning the extent of such application in Malaysia.As Malaysia is a predominantly Muslim country, Islam, through national culture influences organizations.This research is an attempt to provide further insights into the theory and practice of reward management in the local context as Malaysia is implementing Islam Hadhari’s principles in the country.This study also further investigates the relationship between the Malaysian cultural orientation, Islam Hadhari’s principles, environmental factors and perceptions of non-monetary and monetary rewards toward the reward program influences.The other important aim of the study is to identify the moderating role of organizational size between cultural orientations, Islam Hadhari’s principles, environmental factors (internal and external) and perceptions of non-monetary and monetary rewards. The study adopts a quantitative approach using Partial Least Square (PLS) based Structural Equation Modeling (SEM) approach.The study will benefit the human resource practitioners theoretically and practically by providing direction and suggestions in designing and implementing the non-monetary and monetary rewards for Malaysian private organizations from Islamic perspectives.